Agricultural Liberalization in Post-Apartheid South Africa - (:unkn) unknown (My University, 2011)
After the demise of apartheid, the agricultural sector in South Africa went through an unprecedented process of deregulation. This agricultural liberalization has been characterized by the increasing influence of macro-actors, including commercial banks (ABSA and Standard Bank), agricultural engineering firms, and investment funds. New production and financing models are now emerging. The stranglehold on agricultural production by a few macro-actors that are often not even agriculturally orientated but rather part of a globalized capitalist structure stems from the conception of agricultural production merely as a commodity for speculation on the financial markets. Challenges include the status of agricultural producers, sovereignty over food, and regulation of the sector.
Keywords: African Research